Optimalisasi Keaktifan Belajar Melalui Penerapan Model Exo Olo Task Berbantuan Permainan Simkota - Farida Afia Rahma; Syamsul Bachri; Esthi Wahyu Utami (FKIP, Universitas Palangka Raya, 2025)
This study examines the optimization of student learning engagement through the Exo Olo Task learning model using the SIMKOTA game. The background of this research lies in the lack of active student participation in learning activities, highlighting the importance of optimizing engagement to support students in mastering 21st-century skills. The objective of this study is to enhance student engagement in social studies learning. A Classroom Action Research was conducted in Class VIII-8 over two cycles, each consisting of planning, implementation, reflection, and follow-up actions. Data were collected through observation and documentation, and analyzed using both quantitative and qualitative methods. The findings indicate an improvement in engagement levels, from a moderate category in the first cycle to a high category in the second cycle. These results demonstrate that the Exo Olo Task model, integrated with a game-based approach, can significantly optimize student learning engagement